Beyond the Screen: Developing Listening Skills through Disney Narrative Stories - Diah Sukmawati; Mutiarani Mutiarani (Ikatan Dai Indonesia, 2026)
This study investigates the impact of Disney Narrative stories on improving students' listening skills at the junior high school level. A quantitative pre-experimental design involving 23 eighth-grade students was employed. The instruments consisted of pre-test and post-test listening assessments, as well as a validated and reliable instrument (Crobach’s Alpha = 0.910). The results revealed a significant improvement in students’ Listening skills after the treatment. The mean pre-test score was 66.53, increasing to 87.67 on the post-test. A paired sample T-test indicated a statistically significant difference between the two scores (t=-6.666, p < 0.001). The effect size (Cohen’s d = 1.39) demonstrated a very large impact of the intervention. These findings confirm that Disney narrative stories are effective teaching media for enhancing listening skills. The engaging storyline, visual context, and familiar language structures help students improve literal understanding, inferential thinking, vocabulary recognition, and narrative-based audiovisual materials in listening instruction to promote meaningful and enjoyable learning experiences.